2013
DOI: 10.1111/aogs.12235
|View full text |Cite
|
Sign up to set email alerts
|

HE4 and CA125 levels in the preoperative assessment of endometrial cancer patients: a prospective multicenter study (ENDOMET)

Abstract: This study confirmed that the markers are significantly elevated in patients with prognostic high-risk factors and may, therefore, be used as an additional tool in combination with imaging and clinical information when planning the treatment of endometrial cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
57
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 39 publications
7
57
1
2
Order By: Relevance
“…Our results are supported by the results of Antonsen et al, who reported a significantly higher level of HE4, in contrast to CA125, in patients with malignant endometrial pathologies as compared to atypical endometrial hyperplasia. The sensitivity and specificity of HE4 at the cut-off level of 70 pmol/L in their study found that the ability to differentiate malignancy from atypical endometrial hyperplasia was 43.9% and 76.5%, respectively, while the sensitivity and specificity of CA125 at the cut-off level of 35 U/mL were 19.7% and 78.2%, respectively [25]. Our finding are also supported by results of Minar et al, in which a significant higher level of HE4 was found in patients with EC as compared to benign endometrial pathologies [26] In the study of Chen et al a significantly higher level of HE4 was found in patients with uterine cancer as compared to benign uterine disease, among all patients studied and among the premenopausal patients in particular.…”
Section: Discussionmentioning
confidence: 92%
“…Our results are supported by the results of Antonsen et al, who reported a significantly higher level of HE4, in contrast to CA125, in patients with malignant endometrial pathologies as compared to atypical endometrial hyperplasia. The sensitivity and specificity of HE4 at the cut-off level of 70 pmol/L in their study found that the ability to differentiate malignancy from atypical endometrial hyperplasia was 43.9% and 76.5%, respectively, while the sensitivity and specificity of CA125 at the cut-off level of 35 U/mL were 19.7% and 78.2%, respectively [25]. Our finding are also supported by results of Minar et al, in which a significant higher level of HE4 was found in patients with EC as compared to benign endometrial pathologies [26] In the study of Chen et al a significantly higher level of HE4 was found in patients with uterine cancer as compared to benign uterine disease, among all patients studied and among the premenopausal patients in particular.…”
Section: Discussionmentioning
confidence: 92%
“…In Danish Endometrial Cancer Study a cutoff of 20 U/ml for CA125 could detect myometrial invasion of !50% with the sensitivity of 63% and the specificity of 71%, as well as patients with lymph node metastasis with the sensitivity of 86% and the specificity of 53%. At these sensitivities, the specificities for HE4 were 68.9% at cutoff 106 pM and 33.3% at cutoff 49 pM, respectively [40].…”
Section: Discussionmentioning
confidence: 94%
“…There is evidence that the serum tumour markers cancer antigen 125 (CA-125) and, more recently, human epididymis protein 4 (HE-4), are significantly correlated with histological grade, stage, lymph node metastases, myometrial invasion and cervical involvement 6971. However, the appropriate cut-off has not been established and evidence that serum marker assessment is clinically useful is lacking.…”
Section: Surgerymentioning
confidence: 99%